Reducing depressive symptoms and increasing positive feelings with expressive writing - Chen Sung Wong; Melissa Jane Chua; Kususanto Ditto Prihadi (Intelektual Pustaka Media Utama, 2021)
This experimental study examined the effect of expressive writing on depressive symptoms. 86 undergraduate students were recruited from a private university to perform online positive experience writing (PEW) (n=31), negative experience (NEW) (n=32) and control topic (CW) (n=23) for three sessions in three consecutive weeks. The depressive symptoms of participants were measured at pre-treatment and post-treatment. It was hypothesized that PEW has significant greater reduction in depressive symptoms compared to NEW and CW based on broaden and build model. Nevertheless, results showed that PEW had significantly greater symptoms reduction than CW, yet there was no significant difference between PEW and NEW. The findings suggested that PEW might be potentially useful in reducing depressive symptoms among undergraduates.